Tsg101 regulates PI(4,5)P2/Ca2+ signaling for HIV-1 Gag assembly - Ehrlich, Lorna S.; Medina, Gisselle N.; Photiadis, Sara; Whittredge, Paul B.; Watanabe, Susan; Taraska, Justin W.; Carter, Carol A. (Frontiers in Microbiology, 2014)
Our previous studies identified the 1,4,5-inositol triphosphate receptor (IP3R), a channel mediating release of Ca2+ from ER stores, as a cellular factor differentially associated with HIV-1 Gag that might facilitate ESCRT function in virus budding. Channel opening requires activation that is initiated by binding of 1,4,5-triphosphate (IP3), a product of phospholipase C-mediated PI(4,5)P2 hydrolysis. The store emptying that follows stimulates store refilling which requires intact PI(4,5)P2. Raising cytosolic Ca2+ promotes viral particle production and our studies indicate that IP3R and the ER Ca2+ store are the physiological providers of Ca2+ for Gag assembly and release. Here, we show that Gag modulates ER store gating and refilling. Cells expressing Gag exhibited a higher cytosolic Ca2+ level originating from the ER store than control cells, suggesting that Gag induced release of store Ca2+. This property required the PTAP motif in Gag that recruits Tsg101, an ESCRT-1 component. Consistent with cytosolic Ca2+ elevation, Gag accumulation at the plasma membrane was found to require continuous IP3R activation. Like other IP3R channel modulators, Gag was detected in physical proximity to the ER and to endogenous IP3R, as indicated respectively by total internal reflection fluorescence and immunoelectron microscopy or indirect immunofluorescence. Reciprocal co-immunoprecipitation suggested that Gag and IP3R proximity is favored when the PTAP motif in Gag is intact. Gag expression was also accompanied by increased PI(4,5)P2 accumulation at the plasma membrane, a condition favoring store refilling capacity. Supporting this notion, Gag particle production was impervious to treatment with 2-aminoethoxydiphenyl borate, an inhibitor of a refilling coupling interaction. In contrast, particle production by a Gag mutant lacking the PTAP motif was reduced. We conclude that a functional PTAP L domain, and by inference Tsg101 binding, confers Gag with an ability to mod